Cardiac sympathetic nervous activity during myocardial ischemia, reperfusion and ventricular fibrillation in the dog: effects of intravenous lidocaine - Aidonidis, Isaac; Brachmann, Johannes; Seller, Horst; Dembowsky, Klaus; Czachurski, Jürgen; Kübler, Wolfgang (Cardiology, 1992)
In 12 open-chest dogs, cardiac sympathetic nervous activity (CSNA) was recorded before and after occlusion of the left anterior descending coronary artery as well as during reperfusion and ventricular fibrillation (VF). In 7 control animals, CSNA did not significantly differ from preocclusion levels when determined 20 min after occlusion (+3.5 ± 1.5%, mean ± SEM) and up to 15 min following reperfusion (+1.5 ± 0.6%). However, VF was associated with a potential increase in CSNA by 106 ± 15.5%(p < 0.001). The effect of lidocaine (6 mg/kg) on cardiac sympathetic tone was examined in 5 additional animals. Lidocaine reduced control CSNA by 23 ± 4.7% (p < 0.001); subsequent ischemia and reperfusion did not substantially change the level of preocclusion activity. CSNA decreased significantly also during VF (52 ± 4.2%, p < 0.001). In conclusion, efferent CSNA was slightly altered in the course of acute myocardial ischemia and reperfusion, but significantly increased during VF. Lidocaine produced marked attenuation of CSNA in anesthetized dogs.